Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.18632/oncotarget.4657
|View full text |Cite
|
Sign up to set email alerts
|

GL-V9, a new synthetic flavonoid derivative, ameliorates DSS-induced colitis against oxidative stress by up-regulating Trx-1 expression via activation of AMPK/FOXO3a pathway

Abstract: GL-V9, a new synthesized flavonoid derivative, has been reported to possess anticancer properties in our previous studies. Uncontrolled overproduction of reactive oxygen species (ROS) has been implicated in oxidative damage of inflammatory bowel disease (IBD). In this study, we aimed to investigate the protective effect of GL-V9 against dextran sulfate sodium (DSS)-induced colitis. GL-V9 attenuated DSS-induced body weight loss, colon length shortening and colonic pathological damage. GL-V9 also inhibited infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Given that casticin suppresses cell growth in ovarian cancer (SKOV3) cells through FOXO3a activation (13), we aimed to ascertain whether casticin inhibits in vitro carcinogenesis and CSC characteristics in SCLC LCSLCs by activating FOXO3a, a transcription factor inactivated by AMPK (14)(15)(16)24). We first found that casticin significantly increased the phosphorylation levels of AMPK and ACC, in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that casticin suppresses cell growth in ovarian cancer (SKOV3) cells through FOXO3a activation (13), we aimed to ascertain whether casticin inhibits in vitro carcinogenesis and CSC characteristics in SCLC LCSLCs by activating FOXO3a, a transcription factor inactivated by AMPK (14)(15)(16)24). We first found that casticin significantly increased the phosphorylation levels of AMPK and ACC, in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sato et al proposed that metformin efficaciously eliminates glioma stem cell-like cells by activating FOXO3 via AMPK (8). Moreover, Zhao et al provided evidence that GL-V9, a new synthetic flavonoid derivative, improved the state of animals with DSS-induced colitis from oxidative stress by upregulating Trx-1 via activation of the AMPK/FOXO3a pathway (15). However, whether the anticancer effects of casticin involve AMPK/FoxO3a signaling remains undefined.…”
Section: Casticin Suppresses the Carcinogenesis Of Small Cell Lung Camentioning
confidence: 99%
“…Studies revealed that FOXO3α form a complex with PGC‐1α to transactivate their downstream targets, which are mostly antioxidants, such as catalase, MnSOD, peroxiredoxin 3 (PRDX3), peroxiredoxin 5, thioredoxin 2, thioredoxin reductase 2, and uncoupling protein 2 (Nemoto, Fergusson, & Finkel, ). Its involvement in UC has been well analyzed in several studies (Min et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, FoxO proteins are considered as therapeutic targets for cancer (23, 8284), diabetes mellitus (30, 85, 86), and pathways involving oxidative stress (82, 87, 88). Interestingly, FoxO transcription factors also play a significant role in inflammation.…”
Section: Foxo Transcription Factors and Cognitive Lossmentioning
confidence: 99%